Göytepe : Neolithic excavations in the Middle Kura Valley, Azerbaijan - Nishiaki, Yoshihiro; Guliyev, Farhad (Archaeopress Archaeology, 2020)
This volume publishes the first round of fieldwork and research (2008-2013) at Göytepe, a key site for understanding the emergence and development of food-producing communities in the South Caucasus. Results include findings relating to chronology, architecture, technology, social organisation, plant and animal exploitation, and more.